Improving Project Manager Decision with Gamification: An Experience Report - Porto, Daniel de Paula; Ferrari, Fabiano Cutigi; Fabbri, Sandra Camargo Pinto Ferraz (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2019: Anais do XVIII Simpósio Brasileiro de Qualidade de Software, 2019)
Context: Gamification is an emerging subject that has been applied in different areas to bring contributions to different types of activities, including project management activities. Objective: Reporting on an experience of introducing gamification in a real software development company in a peripheral, but relevant for management, software development activity: the timesheet fill. Method: We introduced gamification in software process to motivate team members to fill out their timesheets. The Habitica tool was used to support the gamification. Delays for filling out the timesheets by team members were measured before, within and after the insertion of gamification. Results: We observed a beneficial gamification influence on timesheet fill. Based on historical data and on our measurements, the performance was four times better with gamification when compared with the conventional (i.e. without gamification) approach. Even after gamification removal, the performance remained statistically better than historical records. Conclusion: Gamification improved the attendance on timesheet fulfills and this could help the project manager make the software development more manageable in activities like costs and deadline estimates.